PSYCHOLOGICAL FACTORS OF PROFESSIONAL BURNOUT AND WAYS TO OVERCOME IT IN THE MODERN LABOR MARKET - Алексєєнко-Лемовська, Людмила (SWorldJournal, 2025)
The paper examines the problem of professional burnout as one of the key challenges of the modern labor market. The main psychological factors contributing to the development of burnout are analyzed, as well as ways to prevent and overcome it. Particular